Examination of young children with Lea symbols. Issue 5 (1st May 2002) - Becker, R; Hübsch, S; Gräf, M H; Kaufmann, H
Abstract : Aims: In order to establish normal values and interocular differences of visual acuity, Lea symbols were applied to neurologically and ophthalmologically normal children. Methods: 385 children (21–93 months old) were examined, within a routine check up in an urban paediatric practice where Lea symbol acuity (LS) was measured. Of these children, 90 were re-examined in hospital comparing Lea symbol acuity (LS) and Landolt C acuity (LC). Strabismus, ametropia, and any organic eye disease were excluded. Results: In the paediatric practice, LS could be measured on both eyes in 54% of the children. In the age group above 36 and 48 months the success rate was 76% and 95%, respectively. Acuity in the paediatric practice ranged from 0.1 to 2.0 (median 1.25) in the whole group. Interocular acuity difference was one line or less in 80%. In the hospital, LS and LC could be measured on both eyes of 77% and 48% of the 90 children, respectively. Cooperation increased with age. LS in the hospital ranged from 0.32 to 2.0 (median 1.0) and LC from 0.16 to 1.25 (median 0.8). Interocular difference of LS acuity was one line or less in 90%. Conclusion: Lea symbols were found to be useful for visual acuity assessment in early childhood. Significant variability of visual acuity in this age group is caused by cooperation. When monocular measurements are possible on both eyes, however, the intraindividual interocular difference of visual acuity usually does not exceed one line.